Tax Reforms, Dividend Policy and Trends in Income Inequality Empirical Evidence based on Norwegian Data - Erik Fjærli; Rolf Aaberge (Statistics Norway, Research Department, 2000)
This paper discusses the degree of intertemporal comparability of national estimates of income inequality when data are based on income tax records. The problem of comparability is particular crucial when major tax reforms have taken place and pre- and post-reform income data are used as basis for comparing trends in income inequality. Particular attention is paid to the definition and measurement of income from shares. The conventional wisdom that the increase in inequality in Norway during the 1990's was caused by a rising disequalizing contribution of capital income is questioned by the present results. The rise in income inequality coincided with the implementation of a major tax reform that affected the financing incentives in the corporate sector and the income shifting incentives in small enterprises. Thus, when tax reported dividends are used as a measurement of returns from shares, changes in the estimated income inequality may be a result of changes in the income reporting behavior rather than factual changes in the distribution of income. Our results suggest that the observed rise in income inequality during the 1990's to some extent can be explained by a change in the dividend policy of the corporations, induced by the tax reform in 1992. When the total return from shares is taken into account, we find less increase in the level of inequality and less increase in the contribution to inequality from share ownership.
Keywords: D31; G35; H25; 330; Income definition; capital income; corporate income; tax reform; income inequality